2022
DOI: 10.1136/bcr-2021-246833
|View full text |Cite
|
Sign up to set email alerts
|

Continuous pericapsular nerve group (PENG) block through an elastomeric infusion system, associated with the lateral cutaneous nerve block of the thigh for total hip arthroplasty

Abstract: Orthopaedic surgeries can lead to pain that is difficult to treat, sometimes requiring prolonged hospitalisation. Peripheral nerve blocks stand out as an efficient strategy within the context of multimodal analgesia. The hypothesis is that continuous pericapsular nerve group block, when combined with lateral femoral cutaneous nerve block, can provide excellent analgesic coverage for hip surgeries. Continuous infusion systems can prolong analgesia, minimising opioid consumption, adverse effects and providing fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 16 publications
(13 reference statements)
0
6
0
Order By: Relevance
“…Among PENG block studies that reported no post-procedural quadriceps weakness or made no mention of motor function at all, clinical manifestations of extra-IP spread of local anesthetics either as observed injectate spread to the FIC in ultrasound images [ 42 ], sensory loss of dermatomes corresponding to the femoral nerve [ 43 , 44 , 45 , 46 , 47 , 49 , 50 , 51 ], or an absence of statistically significant difference in quadriceps strength in patients receiving a supra-inguinal fascia iliaca compartment block (SI-FICB) [ 60 , 61 ] were found in nine case reports/series [ 42 , 43 , 44 , 45 , 46 , 47 , 49 , 50 , 51 ] and two RCTs [ 60 , 61 ] (group B). Nine case reports/series [ 1 , 48 , 52 , 54 , 55 , 56 , 57 , 64 , 66 ], one cohort study [ 60 ], and four RCTs [ 62 , 63 , 64 , 65 ] using PENG block specifically reported no motor block at all (group C).…”
Section: Resultsmentioning
confidence: 99%
“…Among PENG block studies that reported no post-procedural quadriceps weakness or made no mention of motor function at all, clinical manifestations of extra-IP spread of local anesthetics either as observed injectate spread to the FIC in ultrasound images [ 42 ], sensory loss of dermatomes corresponding to the femoral nerve [ 43 , 44 , 45 , 46 , 47 , 49 , 50 , 51 ], or an absence of statistically significant difference in quadriceps strength in patients receiving a supra-inguinal fascia iliaca compartment block (SI-FICB) [ 60 , 61 ] were found in nine case reports/series [ 42 , 43 , 44 , 45 , 46 , 47 , 49 , 50 , 51 ] and two RCTs [ 60 , 61 ] (group B). Nine case reports/series [ 1 , 48 , 52 , 54 , 55 , 56 , 57 , 64 , 66 ], one cohort study [ 60 ], and four RCTs [ 62 , 63 , 64 , 65 ] using PENG block specifically reported no motor block at all (group C).…”
Section: Resultsmentioning
confidence: 99%
“…The use of an indwelling catheter was described with a low-volume bolus and infusion pump. [ 5 , 6 ] We had placed a catheter in one patient at 2 mL/h for 5 days as the patient was admitted in the hospital for analgesic titration and was subsequently discharged on 2nd day. The patient had good pain relief and no untoward complications.…”
Section: Discussionmentioning
confidence: 99%
“…Da Costa et al (23), described a case report for analgesia delivered through a continuous infusion via a catheter inserted in the iliopsoas muscle and the iliopubic eminence, for total hip arthroplasty. The study showed that the continuous PENG block via a catheter with an elastomeric pump for 48 hours, plus the femoral cutaneous single dose block, provides an adequate level of analgesia.…”
Section: Observational Studiesmentioning
confidence: 99%